2010
DOI: 10.1103/physrevb.82.075121
|View full text |Cite
|
Sign up to set email alerts
|

Analytical treatment of in-plane magnetotransport in the Falicov-Sievert model

Abstract: We derive an analytical expression which allows efficient computation of the effect of all the Fermi-surface trajectories induced by a combination of Bragg scattering and magnetic breakdown on the in-plane components of the resistivity tensor. The particular network of coupled orbits which we consider was first formulated by Falicov and Sievert, who studied the problem numerically. Our approach, based upon a method used previously to derive an analytical solution for interlayer transport, allows us to show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…9. Building on Falicov and Sievert's treatment of magnetic breakdown for in-plane conductivity 25 , Nowojewski et al showed that this issue can be solved by writing a self-consistent, vectorized form of the Shockley-Chambers tube integral 26,27 . This method has previously been used to study systems wherein ω did not vary with ϕ 23,28 .…”
Section: B Fermi Surface Across the Brillouin Zone Boundarymentioning
confidence: 99%
“…9. Building on Falicov and Sievert's treatment of magnetic breakdown for in-plane conductivity 25 , Nowojewski et al showed that this issue can be solved by writing a self-consistent, vectorized form of the Shockley-Chambers tube integral 26,27 . This method has previously been used to study systems wherein ω did not vary with ϕ 23,28 .…”
Section: B Fermi Surface Across the Brillouin Zone Boundarymentioning
confidence: 99%
“…In addition to calculating σ zz , we can use the same methods as detailed above to calculate the in-plane components of the conductivity tensor 53 . Neglecting the weak interlayer warping of our system, we find v x (ϕ) = m * k F (ϕ) cos(ϕ − γ) and v y (ϕ) = m * k F (ϕ) sin(ϕ − γ).…”
Section: Appendix E: In-plane Transport Simulationsmentioning
confidence: 99%
“…Another powerful method of understanding the shape of simple Fermi surfaces is angledependent magnetoresistance oscillations (AMRO), which allow access to the Fermi surface at much higher temperatures and scattering rates than the purely quantum oscillation effects. This method has been employed successfully to map both quasi-one dimensional (Q1D) and quasi-two dimensional (Q2D) Fermi surfaces, as in BEDT-TTF organic salts 3,4 , intercalated graphite compounds 5 , ruthenates 6 , and superconducting pnictides 7 and cuprates [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%